High treatment success rate among multidrug-resistant tuberculosis patients in Myanmar, 2012–2014: a retrospective cohort study. (17th January 2018) - Thu, Myat K; Kumar, Ajay M V; Soe, Kyaw T; Saw, Saw; Thein, Saw; Mynit, Zaw; Maung, Htet M W; Aung, Si T
Abstract: Background: Since 2011, Myanmar has adopted domiciliary care for multidrug-resistant tuberculosis (MDR-TB) patients and implemented several patient-support measures such as community-based directly observed treatment, nutritional support and financial incentives for patients and providers. We assessed treatment outcomes among MDR-TB patients registered for treatment in the Yangon and Mandalay Regions of Myanmar during 2012–2014 and factors associated with unfavourable treatment outcomes. Methods: We performed a retrospective cohort study involving secondary analysis of routine programmatic data extracted from the electronic MDR-TB treatment registries. We calculated the adjusted risk ratio (aRR) and 95% confidence interval (CI). Results: Of 2185 MDR-TB patients (75% HIV tested, 14% HIV positive with 70% of them receiving antiretroviral therapy), 1746 (80%) were successfully treated (cured and treatment completed) and 20% had unfavourable outcomes (14% died, 3% lost to follow-up, 2% failure and 1% not evaluated). Compared with young patients (<25 y), patients 25–54 y of age (aRR 2.0 [95% CI 1.3 to 2.9]) and >55 y (aRR 3.2 [95% CI 2.1 to 4.8]) were more likely to have unfavourable outcomes. HIV-positive patients (especially not receiving ART; aRR 2.2 [95% CI 1.4 to 3.6]) and patients with 'unknown HIV status' (aRR 1.9 [95% CI 1.5–2.4]) had a higher risk of unfavourable outcomes compared with HIV-negative patients. Conclusions: Treatment success was high and deaths accounted for three-fourths of unfavourable outcomes. Joint care and management of MDR-TB and HIV co-infected patients should be strengthened.